Penilaian Kebutuhan Pelatihan pada Tingkat Individu Petugas Rekam Medis - Helda Budiyanti; Nyoman Anita Damayanti (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2015)
ABSTRACT             The increased number of complaint patient indicated performance gap of medical records officer. Training needs assessment was a systematically order of process to discover and identified the existence of a disparity performance caused by a lack of knowledge, attitude and skills in doing the work. Individual analysis identified a disparity between requirements of work to requirement an organization that owned by their respective employee. The purpose of this study was to develop a training needs medical records staff at Undaan Surabaya Eye Hospital,  based on the training needs assessment through individual analysis.This was a descriptive study, subject of research were medical record officers who works in Undaan Surabaya Eye Hospital. More that 56,00% was included in good category knowledge. The most medical records officers has 88% excellent working attitude, skilled officers medical records in conducted technical work related duties 77.78% good category, and softkills as a whole into the category of a good 49,5%. This study concluded be taken from this study was the training needs of medical record staff in Undaan Eye Hospital Surabaya generally was training on knowledge and skill of management medical records. Keywords :individual analysis, medical record staff, training need assessment